2019
DOI: 10.1111/anu.12928
|View full text |Cite
|
Sign up to set email alerts
|

Growth performance, intestinal morphology, hepatopancreatic antioxidant capacity and growth‐related gene mRNA expressions of juvenile grass carp ( Ctenopharyngodon idellus ) as affected by graded levels of dietary arginine

Abstract: An 8‐week growth trial was conducted to investigate the effects of dietary Arg levels (7.6, 12.3, 17.9, 22.4 and 28.6 g/kg diet) on growth performance, hepatopancreatic antioxidant capacity, intestinal morphology and growth‐related gene expressions of juvenile grass carp (Ctenopharyngodon idellus). The results showed that SGR in Arg22 and Arg28 groups was lower than in Arg12 and Arg17 groups (p < 0.05). Serum NO content in Arg7 group was lower than other groups. Hepatopancreatic GSH‐Px activity was higher in A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 37 publications
0
7
0
Order By: Relevance
“…This may suggest that the high stocking density (HD) tanks lose buffering capacity. However, TAN concentration, pH, alkalinity, water temperature, salinity, and dissolved oxygen were all in a safe range for the culture of grass carp (Chen, Zhang, Tan, Zhou, & Yao, 2019; Liu et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…This may suggest that the high stocking density (HD) tanks lose buffering capacity. However, TAN concentration, pH, alkalinity, water temperature, salinity, and dissolved oxygen were all in a safe range for the culture of grass carp (Chen, Zhang, Tan, Zhou, & Yao, 2019; Liu et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Hevrøy et al (2007) indicated that lower lysine intake could decrease liver IGF‐I expression levels in Atlantic salmon; hence, a deficiency of dietary lysine could explain decreased IGF‐I expression in N. albiflora . However, excess dietary lysine also decreased IGF‐I expression in this study, and the reason may be that excess dietary lysine led to insulin resistance through a negative feedback system (Liang et al, 2016; Um, Alessio, & Thomas, 2006; Chen, Zhang, Tan, Zhou, & Yao, 2019). In this study, the muscle IGF‐IR gene expression of fish fed 13.1 g/kg diet was significantly lower than that of fish fed other diets, indicating that lysine deficiency seems to be compromising the function of IGFs in muscle, which is in agreement with the previous study of Azizi et al (2016), lysine deficiency decreased IGF‐IR mRNA levels.…”
Section: Discussionmentioning
confidence: 55%
“…However, excess dietary lysine also decreased IGF-I expression in this study, and the reason may be that excess dietary lysine led to insulin resistance through a negative feedback system (Liang et al, 2016;Um, Alessio, & Thomas, 2006;Chen, Zhang, Tan, Zhou, & Yao, 2019).…”
Section: F I G U R Ementioning
confidence: 51%
“…The intestinal folds height in each intestine section was determined by a visual micrometre (inverted microscope A200 type, Zeiss, Germany), and the average value was taken as the measurement result according to Yan and Zhou (2006). Two sections of each sample and four villi of each section were randomly selected for measurement according to Chen et al., (2019).…”
Section: Methodsmentioning
confidence: 99%